1962
DOI: 10.1073/pnas.48.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Changes in the Nem-Reactive —Sh Groups of Hemoglobin on Oxygenation-Deoxygenation

Abstract: In a previous communication the reaction of N-ethylmaleimide (NEM) with the thiols of intact human erythrocytes was described.1 The principal sites of reaction are the p-chains of hemoglobin2 and intracellular glutathione. Average values of 2.35 and 0.45 equivalents of HbSH and GSH respectively per mole of hemoglobin have been found for normal red cells. The conditions used were NEM/Hb = 8,-1 hr, 250C, pH 6.8. NEM is relatively unstable above pH 7 and reacts readily with thiols at pH 6.8.3 As shown in Figure 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…As previously observed (Taketa and Morell, 1969) and confirmed here for native hemoglobin, conversion of the cross-linked hemoglobins to the carbonyl derivative slightly decreases the reactivity with DTDP relative to that of the corresponding oxyhemoglobin derivatives. Furthermore, deoxygenation of the cross-linked hemoglobins decreased reactivity of the reactive thiol as previously observed for the native protein (Riggs, 1961;Morell et al, 1962;Benesch and Benesch, 1962). At alkaline pH (8.4) the rate constants for reaction of these proteins with DTDP is increased to the same degree (three-to fivefold relative to those at pH 7.0) as observed for native HbA 0 .…”
Section: Sulfhydryl Reactivitysupporting
confidence: 73%
“…As previously observed (Taketa and Morell, 1969) and confirmed here for native hemoglobin, conversion of the cross-linked hemoglobins to the carbonyl derivative slightly decreases the reactivity with DTDP relative to that of the corresponding oxyhemoglobin derivatives. Furthermore, deoxygenation of the cross-linked hemoglobins decreased reactivity of the reactive thiol as previously observed for the native protein (Riggs, 1961;Morell et al, 1962;Benesch and Benesch, 1962). At alkaline pH (8.4) the rate constants for reaction of these proteins with DTDP is increased to the same degree (three-to fivefold relative to those at pH 7.0) as observed for native HbA 0 .…”
Section: Sulfhydryl Reactivitysupporting
confidence: 73%
“…The high degree of B93C conservation in vertebrates [9], combined with its allosterically-controlled reactivity [13, 17] and high intracellular concentration suggest a prominent functional role in vivo. In the present work, we tested whether the β93Cys residue plays a role within the RBC antioxidant network.…”
Section: Discussionmentioning
confidence: 99%
“…This residue is conserved amongst vertebrates but its function remains unclear. Previous studies have shown that the reactivity of the β93Cys residues towards thiol-reactive agents is allosterically controlled by oxygen-dependent changes in hemoglobin conformation with the β93Cys in the R-state being more reactive towards nitrosating and alkylating agents [1114] and to mercurials [15, 16] than T-state hemoglobin [17]. Moreover, the β93Cys can affect electron transfer reactions and limit ferrous heme-derived superoxide production and reactivity with other RBC components [1821].…”
Section: Introductionmentioning
confidence: 99%
“…The quaternary conformation changes the environment of the βCys-93 residue on the proximal side of the haem. In the R state it is exposed to the solvent and reacts with sulphhydryl reagents [3,[42][43][44]. In the T state, solvent access to the cysteine is impeded by the salt bridges formed in deoxyhaemoglobin [3] and exogenous sulphhydryl reagents react much more slowly.…”
Section: Evidence Of T Statementioning
confidence: 99%